Impacts of an Interdisciplinary Developmental Follow-Up Program on Neurodevelopment in Congenital Heart Disease: The CINC Study - Fourdain, Solène; Caron-Desrochers, Laura; Simard, Marie-Noëlle; Provost, Sarah; Doussau, Amélie; Gagnon, Karine; Dagenais, Lynn; Presutto, Émilie; Prud'homme, Joëlle; Boudreault-Trudeau, Annabelle; Constantin, Ioana Medeleine; Desnous, Béatrice; et al. (Frontiers in Pediatrics, 2020)
Objectives: This study investigates the impact of an early systematic interdisciplinary developmental follow-up and individualized intervention program on the neurodevelopment of children with complex congenital heart disease (CHD) who required cardiac surgery. Study Design: We prospectively enrolled 80 children with CHD: 41 were already followed at our neurocardiac interdisciplinary developmental follow-up clinic from the age of 4 months, while 39 were born before the establishment of the program and therefore received standard health care. We conducted cognitive, motor, and behavioral assessments at 3 years of age. We used one-way multivariate analyses of variance to compare the neurodevelopmental outcome of both groups. Results: Between-group analyzes revealed a distinct neurodevelopmental profile with clinically significant effect size, F (6, 57) = 5.491, P < .001; Wilk's Λ = 0.634, partial η2 = 0.366. Children followed at our clinic demonstrated better receptive language performances (P = 0.048) and tended to show higher scores on visuo-constructive tasks (P = 0.080). Children who received standard health care exhibited greater performances in working memory tasks (P = 0.032). We found no group differences on global intellectual functioning, gross and fine motor skills and behaviors. Referral rates for specific remedial services were higher in patients followed at our neurocardiac developmental follow-up clinic compared to the historical cohort (P < 0.005). Conclusions: Overall, the impact of the developmental follow-up and individualized intervention program on neurodevelopmental outcomes remains subtle. Nevertheless, results, although limited by several factors, point towards an advantage of the children who took part in the program regarding receptive language skills compared to children who received standard health care. This is not to exclude that group differences may be greater with growing age. Further research involving larger cohorts is needed to clearly assess the effectiveness of neurocardiac developmental follow-up programs at school age.